Diabetes Melitus sebagai Komorbiditas Utama terhadap Mortalitas Pasien COVID-19 - Zahra Salsabila; Yani Triyani; Sadiah Achmad (Bandung Conference Series: Medical Science, 2023)
Abstract. Cases of COVID-19 are rapidly increasing and spreading throughout Indonesia and have an impact on the degree of severity and the number of deaths in the population that are affected by the presence of comorbidities. The purpose of this study was to analyze the relationship between comorbidities and mortality in COVID-19 patients. This study uses analytic methods with a cross-sectional research design. Data were obtained from the medical records of inpatients with confirmed COVID-19 at Al-Islam Hospital Bandung for the 2021 period. The statistical test used a univariate data test by looking at the characteristics of COVID-19 patients based on age, sex, and length of stay and using the Chi test -Square to analyze whether there is a relationship between the independent and dependent variables. The number of respondents in this study was 2,047 people, with the most age being ≥60 years (39.5%), male sex (51.3%), with the highest comorbidity diabetes mellitus (41.9%), followed by hypertension (35.7%) and renal disease (12.4%) which have CFR values of 10.1%, 5.9%, and 5.2% respectively. Patients with comorbid diseases have a decreased immune response and the location of ACE-2 receptors is found not only in the respiratory tract but also in other organs such as the pancreas and kidneys. The conclusion shows that there is a relationship between comorbidities and mortality of COVID-19 patients at Al-Islam Hospital Bandung in 2021 with a p-value <0.001 (p <0.05) Abstrak. Kasus COVID-19 dengan cepat meningkat dan menyebar ke seluruh Indonesia serta berdampak pada derajat keparahan dan jumlah kematian populasi yang dipengaruhi oleh adanya komorbiditas. Tujuan penelitian ini adalah menganalisis hubungan komorbiditas dengan mortalitas pasien COVID-19. Penelitian ini menggunakan metode analitik dengan rancangan penelitian cross sectional. Data diperoleh dari rekam medis pasien rawat inap yang terkonfirmasi COVID-19 di Rumah Sakit Al-Islam Bandung Periode 2021. Uji Statistik menggunakan uji data univariat dengan melihat karakteristik pasien COVID-19 berdasarkan usia, jenis kelamin, dan lama rawat inap serta menggunakan uji Chi-Square untuk menganalisis ada tidaknya hubungan antara variable bebas dan terikat. Jumlah responden pada penelitian ini sebanyak 2.047 orang, dengan usia yang paling banyak ≥60 tahun (39,5%), jenis kelamin laki-laki (51,3%), dengan komorbiditas tertinggi diabetes melitus (41,9%), disusul dengan hipertensi (35,7%) dan renal disease (12,4%) yang memiliki nilai CFR berturut-turut 10,1%, 5,9%, dan 5,2%. Pasien dengan penyakit komorbid berada dalam penurunan respon imun serta lokasi reseptor ACE-2 yang ditemukan tidak hanya di saluran respirasi, tetapi juga didapatkan di organ lain seperti pankreas dan ginjal. Kesimpulan menunjukkan terdapat hubungan komorbiditas dengan mortalitas pasien COVID-19 di RS Al-Islam Bandung tahun 2021 dengan nilai p <0.001 (p<0.05)